MINE - mapping the interplay between nature and economy: A digital gateway to the foundations of ecological economics - Malte Faber; Thomas Petersen; Marc Frick; Dominik Zahrnt (University of Heidelberg, Department of Economics, 2018)
MINE - Mapping the Interplay between Nature and Economy is a digital archive and visual map showing the intersection between nature and economy. By focusing on the interconnections between fundamental concepts e.g. of time, thermodynamics, evolution, responsibility and justice, a new concept of economic activity emerges within nature. This leads to new interpretations of current ecological, social and economic problems and, in addition, to an in-depth understanding of the modes of thought and policy needed to find sustainable solutions. On the most fundamental level, the dominant view of Mainstream Economics, which considers nature as part of the economy, Ecological Economics amends this view by the perspective that the economy in its physical side is seen as part of nature. Thus, Ecological Economics complements the strengths of Mainstream Economics on a practical level by interdisciplinary research highlighting, spots which do not receive the attention, by Mainstream Economics, they deserve. The research project that ultimately launched MINE began in the 1970s at the University of Heidelberg, conducted by an interdisciplinary group of scientists around Malte Faber, mainly economists, mathematicians, philosophers and physicists. It has contributed and can be broadly linked to the field of Ecological Economics. MINE digitally summarizes the experiences of this research and the accompanying policy-advising in Germany, the European Union, the US and China. It gives a web-based access to its publications and shapes new networks for scientists, students and practitioners. Following the Introduction (Section 1), this paper explains the MINE project (Section 2) and introduces our methodology (Section 3). In Section 4, we outline 15 concepts and heuristics for tackling the environmental problem. Finally, we provide an outlook for further work (Section 5).
urn:nbn:de:bsz:16-heidok-257043
Keywords: B0; B4; B52; D72; H8; Q53; Q57; 330; Environmental Economics; Ecological Economics; History of Economic Thought; Homo Oeconomicus; Homo Politicus; Thermodynamics; Joint Production; Time; Irreversibility; Evolution; Ethics; Sustainability; Responsibility; Ignorance; Absolute and Relative Scarcity; Methodology; Interdisciplinarity